2022
DOI: 10.1038/s41590-022-01158-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation creates an immune regulatory niche at the meningeal lymphatic vasculature near the cribriform plate

Abstract: Meningeal lymphatic vessels residing in the dural layer above the sinuses of the brain, meninges at the base of the brain, and near the cribriform plate have all been shown to drain fluid, cells, and antigens. We have previously reported that meningeal lymphatics near the cribriform plate undergo VEGFR3-dependent lymphangiogenesis during experimental autoimmune encephalomyelitis (EAE) to facilitate excess drainage. Using single-cell RNA sequencing (scRNA-seq), we report that neuroinflammation changes the pheno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 74 publications
(137 reference statements)
2
27
0
Order By: Relevance
“…This neural system is responsible for our sense of smell. Studies have shown that there are lymphatic vessels in the dura mater adjacent to the cribriform plate, and these vessels appear to access and sample CSF due to gaps in the arachnoid barrier ( Hsu et al., 2019 , 2022 ; Louveau et al., 2018 ). Studies also suggest that CSF can drain through the cribriform plate into the nasal lymphatics that reside outside of the skull ( Kida et al., 1993 ), although this finding is more controversial ( Louveau et al., 2018 ).…”
Section: Defense Of the Nasal Epithelium And Olfactory Bulbsmentioning
confidence: 99%
See 2 more Smart Citations
“…This neural system is responsible for our sense of smell. Studies have shown that there are lymphatic vessels in the dura mater adjacent to the cribriform plate, and these vessels appear to access and sample CSF due to gaps in the arachnoid barrier ( Hsu et al., 2019 , 2022 ; Louveau et al., 2018 ). Studies also suggest that CSF can drain through the cribriform plate into the nasal lymphatics that reside outside of the skull ( Kida et al., 1993 ), although this finding is more controversial ( Louveau et al., 2018 ).…”
Section: Defense Of the Nasal Epithelium And Olfactory Bulbsmentioning
confidence: 99%
“…These data suggest that cribriform plate lymphatics drain primarily into the superficial cervical lymph nodes. During states of neuroinflammation, notable lymphangiogenesis was observed around the cribriform plate that did not occur with lymphatics along the dural venous sinuses ( Hsu et al., 2019 , 2021 , 2022 ; Louveau et al., 2018 ). The vulnerability of the olfactory system to nasal pathogens could explain why lymphatic vessels along the cribriform plate expand so readily in response to inflammatory stimuli.…”
Section: Defense Of the Nasal Epithelium And Olfactory Bulbsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included dendritic cells, myeloid cells, and CD4 + T cells. 49 Interestingly, these lymphatic vessels were further shown to capture and present CNS-derived antigens, with prime access to CSF provided by discontinuity of the arachnoid membrane near the cribriform plate. 49 Beyond EAE, meningeal lymphatic vessels have been reported to play varying roles with regards to improving or exacerbating disease pathology.…”
Section: Lo C Ati On S Of Tr Affi Ck Ing and Of Anti G En Pre S Entat...mentioning
confidence: 99%
“…These concepts have been translated to murine disease models. Autoreactive T cells that recognize myelin oligodendrocyte glycoprotein (MOG) are negatively selected in the meninges [ 28 ] and neuroinflammation induces an immune regulatory niche in local meningeal lymphatic vasculature [ 31 ]. Disruption of meningeal lymphatics diminishes MS [ 32 ], but deteriorates Alzheimer’s disease (AD) [ 33 ] in mouse models.…”
Section: Introductionmentioning
confidence: 99%